Етномузикознавча школа Софії Грици - Руда, Т.; Широкова, Н. (Народна творчість та етнографія, 2008)
The article is dedicated to Sophia Hrytsa’s rich activity in the fields of folkloristics, musicology, culturology, sociology. The authors prove that Sophia Hrytsa is a leader of structural and typological school in the Ukrainian ethnic musicology as well as a founder of new trends and methods in this sphere.